Bridging Strength, Monotonicity, and Word Order Choices in Catalan. Issue 8 (13th September 2020) - Brunetti, Lisa; Mayol, Laia; Villalba, Xavier
ABSTRACT: Three experimental studies are presented testing the choice of a left or a right dislocation in Catalan, depending on the bridging relation between the dislocate and its antecedent. We make the hypothesis that the stronger the anaphoric link between the dislocate and its antecedent, the more appropriate a right dislocation is, whereas the opposite is true for left dislocation. The results of two acceptability judgment experiments partially support our hypothesis: Ratings with right dislocation decrease proportionally to the strength of the anaphoric link; however, it is ratings of canonical sentences (without dislocation at all), rather than of left dislocation, that display the opposite direction. For left dislocation, the picture is more complex and reflects the pragmatic function of this construction as a topic shifter or marker of contrast. A third experiment tests the monotonicity hypothesis, according to which a left dislocation is chosen when the anaphoric relation with the antecedent is either downward monotonic or nonmonotonic, whereas a right dislocation is preferred with an upward monotonic relation. The results partially support such a hypothesis but also further support the importance of taking the pragmatic function of left dislocation into account to explain its choice in discourse by speakers.